AKUNTABILITAS PELAYANAN DALAM PERPANJANGAN SURAT IZIN MENGEMUDI DI KEPOLISIAN RESORT KABUPATEN GOWA - Atrianti, Atrianti; Burhanuddin, Burhanuddin; Taufik, Ahmad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
In general, this study aims to analyze the accountability of SIM renewal at the Gowa Police. The type of research used in this study is a qualitative type in which the research is phenomenological in nature, namely to develop or explain the reality of the events under study. Accountability in Public Services is the obligation to convey accountability and information related to the needs of people who wish to extend their SIM. The results of the study show that accountability for the implementation of SIM extension services in the city of Gowa carried out by the Gowa City Police has not been said to be fully accountable in providing services